(untitled) (Architecture Image Studies, 2025)
Telemedicine has emerged as a key modality to ensure continuity of medical care, particularly in health emergency contexts such as the COVID-19 pandemic. To synthesize the scientific evidence on its impact on patient satisfaction in the health sector, a systematic literature review was conducted following PRISMA 2020 guidelines. Databases such as Scopus, PubMed, SciELO, Web of Science, and EBSCOhost were consulted, identifying 3,157 studies, of which 50 met the inclusion criteria and were selected after a critical reading. Findings reveal that most studies report high satisfaction levels associated with benefits such as accessibility, reduced waiting times, and continuity of care. However, limitations related to the lack of physical interaction, technological barriers, and the need for training were also identified. In conclusion, telemedicine is positioned as an effective and well-accepted tool by patients, especially in contexts with mobility restrictions, highlighting the need for its structural integration into hybrid health systems that prioritize user experience and ensure service quality.